The use of twitter for informing the public in the covid-19 epidemic: Example of health science committee of Turkish ministry - Tanyildizi, Nural Imik; Yildiz, Ilkay (IGI Global, 2022)
The coronavirus disease (COVID-19) has influenced the whole world from the moment it appeared. The epidemic had implications in many different areas of all countries of the world. Turkey is among the countries affected by the COVID-19. In this study, the uses of Twitter and the levels of informing the public of COVID-19 Science Committee Members in Turkey were examined. In this process, it was thought that the public needed more information about the epidemic. In this study, 10 COVID-19 Science Committee Members were determined by drawing lots. Their tweets on Twitter were investigated using both qualitative and quantitative content analysis methods. These tweets were analyzed within the categories determined according to content analysis. This study found that the Twitter posts of members of the scientific committee were important in informing the public. © 2023, IGI Global. All rights reserved.